An empirical model of long-term development for accommodation facilities: the role of smart destination. (6th July 2021) - Digiorgio, Veronica; Renga, Filippo Maria
This paper draws on the literature on innovation and networking in the tourism industry to investigate how the promotional tools developed by destinations - websites for information and booking, mobile apps, e-commerce websites, tourist cards, business intelligence (BI) and customer relationship management (CRM) software - may contribute to the long-term development of accommodations in the territory. A model is created to analyse the impact of destinations' digital tools on booking channels, direct and intermediated (both online and offline), and in turn their effect on revenue. Furthermore, a deeper investigation is conducted to have evidence of possible different output by clustering accommodation facilities by location, typology or clientele. Hypotheses are tested with a generalised linear model and an ordered logistic regression on data retrieved from 1, 226 accommodations distributed in the Italian territory. Empirical results evidence the contribution of smart destinations in increasing the competitiveness of the tourism firms in the same area.